2022
DOI: 10.3390/antiox11091708
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antioxidant Feed and Growth Manipulation on the Redox Regulation of Atlantic Salmon Smolts

Abstract: Accumulating evidence indicates a close relationship between oxidative stress and growth rate in fish. However, the underlying mechanisms of this relationship remain unclear. This study evaluated the combined effect of dietary antioxidants and growth hormone (GH) on the liver and the muscle redox status of Atlantic salmon. There were two sequential experimental phases (EP) termed EP1 and EP2, each lasting for 6 weeks. In EP1, Atlantic salmon were fed either low-(L, 230 mg/kg ascorbic acid (Asc), 120 mg/kg α-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…H 2 O 2 is one of the most common types of ROS. 52 53,54 In this study, we found that the OSO challenge significantly increased the piglet liver H 2 O 2 content and markedly decreased SOD and CAT activities. This is similar to the findings in our prior research that maternal exposure to OSO resulted in higher H 2 O 2 levels and lower activity of CAT and SOD in the liver of offspring, 30 whereas Res supplementa- tion in the OSO group improved the content of H 2 O 2 and restored the CAT and SOD activities.…”
Section: ■ Discussionsupporting
confidence: 51%
“…H 2 O 2 is one of the most common types of ROS. 52 53,54 In this study, we found that the OSO challenge significantly increased the piglet liver H 2 O 2 content and markedly decreased SOD and CAT activities. This is similar to the findings in our prior research that maternal exposure to OSO resulted in higher H 2 O 2 levels and lower activity of CAT and SOD in the liver of offspring, 30 whereas Res supplementa- tion in the OSO group improved the content of H 2 O 2 and restored the CAT and SOD activities.…”
Section: ■ Discussionsupporting
confidence: 51%
“…Activities of tSod, Gpx, Cat, and glutathione reductase (Gr) were measured in 150 mg of homogenized samples, using commercial kits (items 706002 (tSod), 703102 (Gpx), 703202 (Gr), 707002 (Cat); Cayman Chemical Co., Ann Arbor, MI, USA), as previously described [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The read quality checks, alignment, and differentially expressed genes (DEGs) were conducted as described by Yin et al [ 25 ]. In brief, raw RNA-seq reads were trimmed and cleaned by TrimGalore!…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations